Uji Efektivitas Nanogel Kombinasi Ekstrak Daun Alpukat (Persea americana mill) Dan Daun Talas (Colocasia esculenta L.) Terhadap Penyembuhan Luka Bakar Pada Kulit Mencit Putih Jantan (Mus musculus) - Ririn Anjelin; Indah Uminawati; Sukma Oktafiani Putri; Yova Aditiatama (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Burns are skin tissue damage that requires intensive treatment to prevent infection and accelerate cell regeneration. The combination of avocado leaf extract (Persea americana Mill.) and taro leaf extract (Colocasia esculenta L.) contains secondary metabolites such as flavonoids, saponins, and tannins that have the potential to heal burns. This study aims to formulate a nanogel preparation combining the extracts of the two plants and test its effectiveness in healing burns in male white mice. The extracts are combined in the form of nanogel preparations to increase the effectiveness of burn healing in mice. The preparations are made in three formula variations (F1, F2, and F3) and evaluated for their physical qualities including organoleptic, pH, spreadability, adhesion, stability (cycling test), irritation, and particle size (PSA). The results showed that the nanogel preparations met all physical quality standard parameters with particle sizes in the nano range. In vivo effectiveness tests for 14 days showed that all nanogel formulas were significantly able to accelerate burn healing compared to negative controls (p < 0.05). Formula 3 (F3), with the highest concentration, provided optimal healing effectiveness, equivalent to the positive control, with a healing percentage of 70% on day 14 and characterized by the fastest reduction in wound diameter. In conclusion, the nanogel preparation combining avocado and taro leaf extracts is effective in healing burns and meets the physical characteristics standards for nanogel preparations.